Strategi Positioning dalam Persaingan Bisnis (Points of Difference dan Points of Parity) - Heri Yadi (Asian Journal of Innovation and Entrepreneurship, 2018)
The purpose of this research is to analyze how Wuling Confero positioning strategy as a newcomer in LMPV (Low Multi-Purpose Vehicle) competition in Indonesian automotive market. The presence of Wuling Confero makes the car sales competition in the LMPV segment becomes increasingly tight. The results show, although as a newcomer, Wuling Confero able to demonstrate its capability in competing with Japanese products that have long dominated the domestic automotive market. The attributes in Points of Difference and Points of Parity offered by these products are able to attract market attention and provide significant success for them in the automotive business competition in Indonesia in LMPV segment. Wuling Confero's sales figures, which reach thousands of units in just a few months since it was launched to the market, indicate that this new product is in demand by Indonesian automotive consumers.